2021
DOI: 10.3389/fpubh.2021.797694
|View full text |Cite
|
Sign up to set email alerts
|

Online Medical Teaching in China During the COVID-19 Pandemic: Tools, Modalities, and Challenges

Abstract: Background: The novel coronavirus disease 2019 (COVID-19) pandemic has tested the ability of universities to provide a high-quality, safe educational experience for students due to campuses shutting down. As a result, online learning could shift from a traditional classroom teaching mode and make education accessible to students. Previous studies have used individual online teaching cases to exploit a variety of online learning tools to ensure the continuation of medical education during this difficult time in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Hanafy et al (18) also found that students favored conventional over online teaching. However, in other studies, students' perceptions positively preferred online courses (19). Our cohort reported major engagement and student-faculty interaction issues, consistent with the recent reports (20)(21)(22).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hanafy et al (18) also found that students favored conventional over online teaching. However, in other studies, students' perceptions positively preferred online courses (19). Our cohort reported major engagement and student-faculty interaction issues, consistent with the recent reports (20)(21)(22).…”
Section: Discussionsupporting
confidence: 91%
“…Collectively, in our cohort, around two-thirds of students and faculty members favored either blended or online courses, while slightly over one-third preferred a traditional face-to-face course format. Likewise, Su et al ( 19 ) concluded that flipped classroom teaching could encourage student-centered independent learning while using online courses.…”
Section: Discussionmentioning
confidence: 99%
“…These new possibilities were also keenly observed by Su et al who reviewed hundreds of local publications on the implementation, challenges, and perspectives of virtual classrooms for medical education during COVID-19 and beyond. The publications reviewed were drawn from 2 main local databases: China National Knowledge Infrastructure (CNKI) and The VIP Chinese Journal Platform [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Educators have been continuously pursuing effective teaching modes, including the postgraduate education paradigm ( 7 , 13 , 34 , 51 ). The traditional classroom has been in existence for hundreds of years.…”
Section: How To Turn the Disadvantages Of Online Teaching Into Advant...mentioning
confidence: 99%
“…It was hardly conceivable that from the beginning of 2020, online education could replace the face-to-face teaching approach in the classroom with such an abrupt transition as a result of the sudden outbreak of the coronavirus disease 2019 (COVID-19) pandemic. However, in response to the Chinese Ministry of Education's policy requirements of “disrupted classes, uninterrupted learning”, online education, which had previously played an auxiliary and experimental role, has swept through China's basic and higher education almost overnight ( 3 , 5 – 7 ). Teachers and students suffering through this extraordinary period have undergone changes from being caught off guard and preparing nervously to resisting and silently accepting online teaching and then to gradually groping for a normal and orderly method ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%